Market Overreaction and Price Reversal in Indonesian Stock Exchange - Kris Brantas Abiprayu; Ascariena Rafinda; Bayu Wiratama (Management Analysis Journal, 2022)
Capital market is a market that all prices that occur should be caused because the market mechanism that has been in such a way able to respond to all the information that exists automatically. Such a market is a market that conforms to the concept of an efficient market. In an efficient market, market participants or investors, will not be able to gain an edge over other investors in terms of investment decisions based on the information they get. The market efficiently assumes that the information that is in the market can be accessed by all actors. In fact, many anomalies occur in the market that break through all assumptions built by the concept of an efficient market, one is the phenomenon of price reversal. Price reversal is a phenomenon in which the price of a stock instrument that suddenly experiences a price reversal because there is information that enters the market and is responded to excessively (overreaction) by the market. Research uses quantitative paradigms to prove a particular hypothesis built into research. The data used is secondary data obtained using stock transaction data as well as financial statement data of each sample company.